A educação sexual na concepção e prática de professores de biologia do ensino médio - Magalhães, Kécia Priscilla Palombello (2016)
Some science teaching studies have emphasized the importance of sexual education in the school, as well as difficulties faced by teachers to fully promote it, considering, in addition to conceptual and scientific aspects, questions that involve the personal and social development of the individual. This study was of a qualitative nature and investigated how high school biology teachers understand and develop sexual education in their classrooms. To this end, eleven teachers were interviewed using semi-structured interviews. The interviews were guided by a list of questions related to sexual education, involving family, school and professional factors. The data was analyzed following the content analysis assumptions and compared to the theoretical framework that supported the research. As regards the results, we highlight some of the categories that emerged from the responses of the participants: responsibility of the school in sexual education, understanding of sex and sexuality, difficulties to develop sexual education in the school, view on sexual orientation recommended in the national curriculum parameters and influence of the national curriculum parameters in the pedagogical experience of the teacher. The teachers indicated difficulties to develop sexual education such as the incomprehension of the parents, immaturity of the students and lack of support of the pedagogical team. We demonstrate that some of the interviewees have a traditionalist view of sexual education, which does not mobilize students to construct this knowledge. Only a part of those surveyed showed concern and commitment as regards the sexual education of students. Therefore, we see the necessity to rethink the curricula of the courses of biology and sciences and invest more intensely in the continuing education of teachers of these areas, so as to fill gaps in the initial education of these teachers, enabling them to develop a sexual education based on social, cultural, psychological and emotional aspects, in addition to the biological.